Hope, coping, and relationship quality in mothers of children with Down syndrome - High, Jessica D. (Kansas State University, 2015)
Parenting a child with Down syndrome may pose unique challenges for parents’ relationship quality. Structural equation modeling was used with a sample of 351 mothers of children with Down syndrome to test if hope mediated the associated between various coping behaviors and relationship quality. Results indicated a greater degree of religious coping and internal coping were each significantly associated with more hope, whereas support seeking was not related with more hope. Higher hope was significantly associated with greater relationship quality. An indirect effect from both religious coping and internal coping to hope, and then hope to relationship quality was identified. Implications for family professionals and future research are discussed.
Keywords: Down syndrome; Parenting; Relationship quality; Individual & Family Studies (0628)